Net mineral requirements of dairy goats during pregnancy - Härter, C. J. [UNESP]; Lima, L. D. [UNESP]; Castagnino, D. S. [UNESP]; Silva, H. O. [UNESP]; Figueiredo, F. O.M. [UNESP]; St-Pierre, N. R.; Resende, K. T. [UNESP]; Teixeira, I. A.M.A. [UNESP] (Elsevier, 2017)
Mineral requirements of pregnant dairy goats are still not well defined; therefore, we investigated the net Ca, P, Mg, Na and K requirements for pregnancy and for maintenance during pregnancy in two separate experiments. Experiment 1 was performed to estimate the net Ca, P, Mg, Na and K requirements in goats carrying single or twin fetuses from 50 to 140 days of pregnancy (DOP). The net mineral requirements for pregnancy were determined by measuring mineral deposition in gravid uterus and mammary gland after comparative slaughter. In total, 57 dairy goats of two breeds (Oberhasli or Saanen), in their third or fourth parturition, were randomly assigned to groups based on litter size (single or twin) and day of slaughter (50, 80, 110 and 140 DOP) in a fully factorial design. Net mineral accretion for pregnancy did not differ by goat breed. The total daily Ca, P, Mg, Na and K requirements for pregnancy were greatest in goats carrying twins (P<0.05), and the requirements increased as pregnancy progressed. Experiment 2 was performed to estimate net Ca, P, Mg, Na and K requirements for dairy goat maintenance during pregnancy. In total, 58 dairy goats (Oberhasli and Saanen) carrying twin fetuses were assigned to groups based on slaughter day (80, 110 and 140 DOP) and feed restriction (ad libitum, 20% and 40% feed restriction) in a randomized block design. The net Ca, P and Mg requirements for maintenance did not vary by breed or over the course of pregnancy. The daily net requirements of Ca, P and Mg for maintenance were 60.4, 31.1 and 2.42 mg/kg live BW (LBW), respectively. The daily net Na requirement for maintenance was greater in Saanen goats (11.8 mg/kg LBW) than in Oberhasli goats (8.96 mg/kg LBW; P<0.05). Daily net K requirements increased as pregnancy progressed from 8.73 to 15.4 mg/kg LBW (P<0.01). The findings of this study will guide design of diets with adequate mineral content for pregnant goats throughout their pregnancy.
Keywords: gestation; major mineral; net requirements; Oberhasli; Saanen